2016
DOI: 10.1515/applirev-2016-1001
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the lexico-grammatical resources of a non-native user of English: The case of can and could in email requests

Abstract: Investigating the lexico-grammatical resources of a non-native user of English: The case of can and could in email requests Abstract: Individual users of English as a first or second language are assumed to possess or aspire to a monolithic grammar, an internally consistent set of rules which represents the idealized norms or conventions of native speakers. This position reflects a deficit view of L2 learning and usage, and is at odds with usage-based approaches to language development and research findings on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…But they also point out that CLI still plays a major role. This is confirmed also by Hall et al (2017), who investigated the ways in which input interacts with other learning factors to shape lexico-grammatical features in the idiolect of a single expert user of L2 English. The UBL approach is likely to have particularly dramatic effects on SLA theory and our understanding of L2 Englishes in coming years, perhaps overturning several long-held assumptions.…”
Section: Usage-based Approachesmentioning
confidence: 67%
See 1 more Smart Citation
“…But they also point out that CLI still plays a major role. This is confirmed also by Hall et al (2017), who investigated the ways in which input interacts with other learning factors to shape lexico-grammatical features in the idiolect of a single expert user of L2 English. The UBL approach is likely to have particularly dramatic effects on SLA theory and our understanding of L2 Englishes in coming years, perhaps overturning several long-held assumptions.…”
Section: Usage-based Approachesmentioning
confidence: 67%
“…He found that internal factors such as short-term memory capacity were better predictors of vocabulary size and accuracy with verbal morphology than external factors such as the richness of the input environment. Like Hall et al (2017), he concludes that his findings are consistent with UBL, but that input is not the whole story. All the evidence so far suggests that, contrary to the UG position, the development of English (and by extension other languages) is not fully constrained by universal principles.…”
Section: Individual Differencesmentioning
confidence: 89%
“…In Hall (2013) I called these 'I-REGISTERS'. Although uncommon as an object of research, aspects of English I-REGISTERS are inferred in corpus studies by Mollin (2009) and Barlow (2013) for L1 users, and Hall et al (2017a) for an L2 user. Eskildsen (this volume) reports on his own research tracing changes in L2 I-ENGLISHES through time.…”
Section: English As Cognitive Resourcementioning
confidence: 99%
“…The chapter is organized as follows. In Section 2, I develop the ontological taxonomy I have previously used to tease apart the concepts expressed by the word language, in applied linguistics (Hall, 2013), in TESOL (Hall et al, 2017b), and in non-native usage (Hall et al, 2017a;Hall, 2018). The following two sections map the entity types identified in the taxonomy onto English as constituted by the two sets of resources, processes, and products identified above.…”
Section: Introductionmentioning
confidence: 99%
“…However, many recent studies indicate a growing interest in the study of variation between individual language users, owing both to the increasing availability of large, diverse and richly annotated datasets and to the finding that these differences do matter in the description of language use. Accordingly, studies have indicated substantial individual differences in grammar (Dąbrowska 2012), collocational preferences (Mollin 2009), n-gram profiles (Barlow 2013;Wright 2017) and lexico-grammatical patterns (Hall et al 2017). Vetchinnikova (2017) explicitly sets language representation at the individual level against the communal level, at which language is normally described using data aggregated from a population of individuals, and argues that they can be qualitatively different from each other, in the same way as different dialects of a language are both different from each other and from the 'standard'.…”
Section: Introductionmentioning
confidence: 99%